An integrated system using phenylboronic acid functionalized magnetic beads and colorimetric detection for Staphylococcus aureus. (March 2022) - Wang, Zhengzheng; Liu, Ju; Chen, Guanhua; Feng, Xiaoyan; Deng, Mei; Mu, Dan; Xu, Qian; Xu, Hengyi
Abstract: Staphylococcus aureus ( S. aureus ) is a common pathogen that can cause severe foodborne diseases. Therefore, the detection of S. aureus in food has been the focus of attention. In this study, a strategy for the detection of S. aureus using magnetic separation technology combined with colorimetry was proposed. Phenylboronic acid, as a compound that had been widely used in the identification of sugars and sugar-based molecules, can selectively enrich compounds with cis -diol groups through a reversible esterification reaction. Hence, 3-aminophenylboronic acid (APBA) could be used as a recognition molecule to capture bacteria, because there were a large amount of peptidoglycan and lipopolysaccharide on the surface of Gram-positive bacteria and Gram-negative bacteria. At the same time, there are few studies on the use of APBA as magnetic separation recognition molecule to enrich pathogenic bacteria. Therefore, we prepared APBA-functionalized magnetic beads (APBA-MBs) for pre-enrichment of S. aureus and an APBA-MBs based untargeted magnetic separation was constructed to replace the traditional targeted magnetic separation. In order to realize the output signal and guarantee the specificity for detecting S. aureus, we used HRP-pig IgG because the Fc fragment of IgG could bind the protein A on the cell wall of S. aureus . Finally, the tetramethylbenzidine (TMB) color development solution was occurred the chromogenic reaction under the action of the HRP enzyme. Under the optimal experimental conditions, the limit of detection (LOD) of the APBA-MBs combined with color reaction was 3.0 × 10 2 CFU/mL in pure culture, fruit juice, pool water and spinach. Highlights: Using APBA to replace expensive recognition molecules such as antibiotics. The CE of S. aureus can reach 90%–100% in the range of 10 6 to 10 1 CFU/mL . The strategy has good performance in different matrixes. The strategy can realize the detection of S. aureus within 2 h.